IMPROVEMENT OF ACCOUNTING AND CONTROL SUPPORT OF EXPORT AND IMPORT OPERATIONS OF ENTERPRISES (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article examines accounting and control support for export-import operations of enterprises in the context of management accounting of these operations. It was determined that today there are problems with the accounting of information on the costs of export-import operations, which do not allow enterprises to fully calculate the effectiveness of conducting foreign economic activities.Each enterprise implements management accounting personally, the current legislation allows adding new ones to the list of sub-accounts with preservation of sub-account codes according to the Chart of Accounts, based on the needs of management, control, analysis and reporting of the enterprise. This measure will allow the enterprise to receive more detailed, specific information, which will help the management staff in planning, analysis and control of the accounting and control support of export-import operations, to make decisions, for the effective implementation of their activities.As a result of the study of the problems of accounting and control support for export-import operations, additional accounts for accounting of income and expenses of foreign economic activity, which will be kept according to geographical and economic segments, as well as an algorithm for the formation of a corresponding management report on financial results, which reflects these additional incomes and additional expenses, are proposed arising during the implementation of this activity. According to the given algorithm for calculating the absolute and relative efficiency of the enterprise's export activity, in the future it is possible to calculate the absolute and relative efficiency of each individual export operation, which will provide the necessary information for the process of making managerial decisions regarding the selection of the most effective types of products.Thus, the effectiveness of the export operation is determined not only by the amount of costs incurred by the exporter during the operation, but also by other factors, including the correct determination of the customs value, which depends on the amount of taxes paid.
Keywords: accounting and control support, management accounting, administrative expenses, sales expenses, geographic and economic segments, management reporting.